Redefining a rights-based approach in the context of temporary labour migration in Asia - Nicola Piper; Stuart Rosewarne; Matt Withers (United Nations Research Institute for Social Development (UNRISD), 2016)
This paper analyses the implications of the dominant framework that has so far guided migration policy in Asia and shaped intra-Asian migration patterns and dynamics. It identifies institutional gaps that hamper the realization of migrants' human and labour rights in East, Southeast, South and West Asia. The key argument advanced is that the dominant project of migration governance continues to fail in several key areas, reflected in decent work deficits in relation to labour rights, the nature of employment opportunities and lacking social protection at all stages of the migration process. The authors find that these manifestations of precarity are related to forces of structural inequalities that operate throughout the global (and regional) economy, institutional incapacity and lacking integration of labour governance within migration governance. They propose that migration governance will only deliver on its commitment to "benefit all" if it is grounded in a holistic understanding of the concept of precarity that takes account of its spatial, protracted and temporal foundations.
Additional information: Addressing Multiple Forms of Migrant Precarity: Beyond “Management” of Migration to an Integrated Rights-Based Approach
Keywords: 330